Genotypic characteristics of a Mycobacterium sp. isolated from yellowtail Seriola quinqueradiata and striped jack Pseudocaranx dentex in Japan. (27th January 2013) - Imajoh, Masayuki; Sugiura, Hidehiro; Hashida, Yumiko; Hatai, Kishio; Oshima, Syun‐ichirou; Daibata, Masanori; Kawai, Kenji
Abstract In Japan, a Mycobacterium marinum‐like mycobacterium was isolated from the yellowtail, Seriola quinqueradiata. The species was identified as M. marinum by a commercial mycobacterial DNA‐DNA hybridization kit. Nevertheless, PCR restriction analysis of the DNA of its RNA polymerase β‐subunit gene definitively showed that this Mycobacterium sp. was M. ulcerans. PCR analysis revealed the genotypic characteristics of M. ulcerans in the Mycobacterium sp., only the mup053 gene sequence being absent, as has been found previously in other piscine mycobacteria such as M. marinum strains DL240490 and DL045 and M. pseudoshottsii. With one exception, this Mycobacterium sp. and M. pseudoshottsii had identical 16S rRNA gene sequences, which is also probably true of M. marinum strains DL240490 and DL045. Similarly, according to comparisons of the 16S rRNA gene, ITS region, and hsp65 gene sequences, this Mycobacterium sp. is more closely related to M. pseudoshottsii than to M. ulcerans or M. marinum. A PCR product of approximately 2000 bp was amplified from region of difference 9 in the Mycobacterium sp. The nucleotide sequence revealed insertion of IS2404, the sequence of which is 1366 bp long. The novel single nucleotide polymorphisms identified in this region distinguished this Mycobacterium sp. from M. marinum strain DL240490 and M. pseudoshottsii. The present findings raise the possibility that these species have a common ancestor. Further studies are required to improve our understanding of the relationship between their geographical origin and genetic diversity.